Interstitial cystitis or bladder pain syndrome: a modern view of a problem - V. F. Onopko; E. A. Kirilenko; E. O. Baranova; V. S. Golubeva (Acta Biomedica Scientifica, 2016)
The review of domestic and foreign literary sources for 2002-2014 made it possible to deepen into the problem of interstitial cystitis and put together different points of view and also to systematize the store of knowledge. Interstitial cystitis is a complex disease with marked clinical manifestation and defeat of urinary bladder with varying severity. For the purpose of diagnostics and treatment optimization of the disease in point in the review they presented the criteria whose existence will make it possible to make the diagnosis of interstitial cystitis. The multifactorial etiology of the disease requires the multiplane causal and pathogenetic therapy but more often empirical and symptomatic In the article describe the algorithm of treatment of patients with the diagnosis of interstitial cystitis.